2022
DOI: 10.1158/0008-5472.can-21-2542
|View full text |Cite
|
Sign up to set email alerts
|

Immune Determinants of the Association between Tumor Mutational Burden and Immunotherapy Response across Cancer Types

Abstract: The FDA has recently approved a high tumor mutational burden (TMB-high) biomarker, defined by {greater than or equal to}10 mutations/Mb, for the treatment of solid tumors with pembrolizumab, an immune checkpoint inhibitor (ICI) that targets PD1. However, recent studies have shown that this TMB-high biomarker is only able to stratify ICI responders in a subset of cancer types, and the mechanisms underlying this observation have remained unknown. The tumor immune microenvironment (TME) may modulate the stratific… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…The MT group showed increased TNB, increased immune infiltrating cells, and upregulated checkpoint molecules, which suggested noticeable immune-supportive features (25). A high level of M1 macrophage cells has been reported to be positively correlated with TMB-H, mainly because M1 macrophages can provide an anti-tumor environment by fostering an inflammation response against tumor-activating CD8 T cells (5). Follicular helper T cells were identified as positively correlated with increased B cell activation capacity, which could help include local antibodies in predicting tumor response to immunotherapy (26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MT group showed increased TNB, increased immune infiltrating cells, and upregulated checkpoint molecules, which suggested noticeable immune-supportive features (25). A high level of M1 macrophage cells has been reported to be positively correlated with TMB-H, mainly because M1 macrophages can provide an anti-tumor environment by fostering an inflammation response against tumor-activating CD8 T cells (5). Follicular helper T cells were identified as positively correlated with increased B cell activation capacity, which could help include local antibodies in predicting tumor response to immunotherapy (26).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, with the increasingly abundant tumor sequencing data published in the literatures and The Cancer Genome Atlas (TCGA) database, studies in cancer prognosis and therapy-related biomarkers have been conducted to address crucial clinical questions. Sinha et al identified that M1 macrophages and dendritic cells were strongly correlated with high TMB, which could stratify the immunotherapy responders well (5). Chen et al identified that the apolipoprotein B mRNA editing enzyme, catalytic polypeptide-like (APOBEC) signature was significantly associated with ICIs therapeutic efficacy in NSCLC (6).…”
Section: Introductionmentioning
confidence: 99%
“…The immune microenvironment, over the past decade, has been extensively investigated because of the remarkable advances in immunotherapy. 27 28 The tumor stroma Open access is composed of an extracellular matrix including nontumor cells of various lineages containing immune cells. 29 30 TLSs provide a vital microenvironment for the cellular immune response directed against tumor cells and are regarded as a predictor of a favorable prognosis in various solid cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Although the U.S. Food and Drug Administration (FDA) has approved pembrolizumab, an ICI targeting PD1, for individuals with TMB-High (defined as ≥10 mutations/Mb) solid tumors (41), evidence showed high TMB failed to predict response to ICIs across all cancer types including breast cancer, prostate cancer, and glioma (42). Recent research indicated that high levels of M1 macrophages and low resting dendritic cells in the TME characterized cancer types with high TMB power including cholangiocarcinoma (43). In our study, the result that two patients with high TMB displayed completely different responses to immune-combined therapy might support the possible fact that TMB was still not a determined predictor of immunotherapy in ICC.…”
Section: Discussionmentioning
confidence: 99%